Timing of introduction to solid food, eczema and wheezing in later childhood: a longitudinal cohort study - Curtis J. D'Hollander; Charles D. G. Keown-Stoneman; Catherine S. Birken; Deborah L. O'Connor; Jonathon L. Maguire; TARGet Kids! collaboration (BMC, 2023)
Abstract Background The timing of introduction to solid food has been associated with eczema and wheezing in childhood. Our aim was to determine whether differences persist within the recommended 4 to 6 month age range. Methods A longitudinal cohort study with repeated measures was conducted among children from birth to 10 years of age who were participating in the TARGet Kids! practice based research network in Toronto, Canada. The primary exposure was the timing of introduction to infant cereal as the first solid food. The primary outcome was eczema and the secondary outcome was wheezing collected by parent report using the validated International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire. Multinomial generalized estimating equations were used and effect modification by family history of asthma and breastfeeding duration were explored. Results Of the 7843 children included, the mean (standard deviation) age of introduction to infant cereal was 5.7 (1.9) months. There was evidence for family history of asthma and breastfeeding duration to be effect modifiers in the eczema (P = 0.04) and wheezing (P = 0.05) models. Introduction to infant cereal at 4 vs. 6 months of age was associated with higher odds of eczema (OR 1.62; 95% CI: 1.12, 2.35; P = 0.01) among children without a family history of asthma who were not breastfeeding when solid foods were introduced. Introduction to infant cereal at 4 vs. 6 months of age was associated with a higher odds of wheezing (OR 1.31; 95% CI: 1.13, 1.52; P < .001) among children without a family history of asthma who were breastfeeding when solid foods were introduced. There was little evidence of an association among the remaining strata for either outcome. Conclusion The findings of this study support recommendations to introduce solid food around 6 months of age.